Effects of Exogenous Hydrogen Sulfide in the Hypothalamic Paraventricular Nucleus on Gastric Function in Rats - Li, Chenyu; Sun, Hongzhao; Shi, Yuan; Yu, Yan; Ji, Xiaofeng; Li, Enguang; Zhou, Xiaofan; Liu, Xiaomeng; Xue, Xikang; Sun, Haiji (Frontiers in Pharmacology, 2022)
Background: Hydrogen sulfide（H2S） is a new type of gas neurotransmitter discovered in recent years. It plays an important role in various physiological activities. The hypothalamus paraventricular nucleus（PVN）is also an important nucleus that regulates gastric function. This study to clarify the role of H2S in the paraventricular nucleus of the hypothalamus in the gastric function of rats. Methods: Immunofluorescence histochemistry double-labeling technique to determine whether there are CBS and c-Fos neurons involved in stress in PVN. Through microinjection of different concentrations of NaHS, physiological saline（PS）, D-AP5, pyrrolidine dithiocarbamate （PDTC）,observe gastric motility and gastric acid secretion effect. Result：After 1h of restraint and immersion C-Fos and CBS co-expressed the most positive neurons after 1h of restraint and immersion, followed by 3h, and the least at 0h. After injection of different concentrations of NaHS into the PVN, it was found to significantly inhibit gastric motility and promote gastric acid secretion in rats (P <0.01), while injection of normal saline, D-AP5 and PDTC did not change significantly (P> 0.05). The suppressive effect of NaHS on gastrointestinal motility and promotional effect of NaHS on gastric acid secretion could be prevented by D-AP5, the specific N-methyl-D-aspartic acid (NMDA) receptor antagonist and PDTC, a NF-κB inhibitor. Conclusions: There are neurons co-expressing CBS and c-Fos in the PVN, and the injection of NaHS into the PVN can inhibit gastric motility and promote gastric acid secretion in rats, and its effect may be through NMDA receptors and NF- κB signaling pathway.